The Effectiveness of Using NPK Compound Fertilizer on the Growth and Yield of Mustard Plants (Brassica juncea L.) - Budi Utomo (Agricultural Science, 2022)
This study aims to determine the extent to which the effectiveness of using NPK compound fertilizer on the growth and yield of mustard plants. This study used a simple randomized block design (RBD) consisting of eight treatments with three replications and for observation, each treatment was represented by two sample plants. The placement of the treatments in the experimental plots was carried out randomly, the growth and yield variables of the mustard plants observed in this study were the length of the plants, observed at the age of 10 days, 20 days and 30 days after transplanting, the number of leaves were observed at the ages of 10 days, 20 days and 30 days after transplanting and plant wet weight. This was done when the plants were 30 days after transplanting. While the results of the study showed a significant effect on the observation variables of plant length, number of leaves and fresh weight of mustard plants due to the use of NPK compound fertilizer and effective (effective) doses in the use of NPK compound fertilizer during growth and yield of mustard plants tended to be achieved by treatment with doses of NPK compound fertilizer. 250 kg per hectare, although the highest growth and yield tended to be shown in the treatment of 350 kg of NPK compound fertilizer per hectare, followed by the treatment of 300 kg of NPK compound fertilizer per hectare.